2019
DOI: 10.2478/cipms-2019-0029
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinesterase and antioxidant activities of foliar extract from a tropical species: Psidium guajava L. (Myrtaceae) grown in Algeria

Abstract: Guava (Psidium guajava L.) is a fruit tree largely used in folk medicine in tropical and subtropical areas. This exotic species was introduced in a botanical garden in the northeast of Algeria in the 1950’s. The aim of this study is to estimate, for the first time, the antioxidant and anticholinesterase activities of chloroform, ethyl acetate and n-butanol extracts of P. guajava growing in Algeria. Six antioxidant assays were tested, results showed very important efficiency in free radical scavenging, reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Previous research [ 6 12 ] reported that Psidium guajava had antioxidant capacity. There was no research concerning the antioxidant capacity of different extracts (n-hexane, ethyl acetate, and ethanol) of leaves and fruit from crystal guava (“ Psidium guajava L.”“crystal”) which is grown in Cianjur, West Java-Indonesia, using three methods (DPPH, CUPRAC, and FRAP).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research [ 6 12 ] reported that Psidium guajava had antioxidant capacity. There was no research concerning the antioxidant capacity of different extracts (n-hexane, ethyl acetate, and ethanol) of leaves and fruit from crystal guava (“ Psidium guajava L.”“crystal”) which is grown in Cianjur, West Java-Indonesia, using three methods (DPPH, CUPRAC, and FRAP).…”
Section: Resultsmentioning
confidence: 99%
“…Manikandan et al [ 8 ] showed that ethanol leaves extract had the highest antioxidant activity using the DPPH method than methanol and water extract, by Soxhlet extraction. The study by Bouchoukh et al [ 6 ] demonstrated that guava leaves from Algeria had the highest antioxidant activity in ethyl acetate extract, when compared to butanol and chloroform extracts, using the DPPH method, while with the CUPRAC method, the highest antioxidant activity was given by butanol [ 6 ]. The study by Ashraf et al [ 7 ] using guava from Pakistan showed that n-hexane leaves extract had the lowest antioxidant activity, compared to methanol and chloroform extracts, using DPPH and FRAP methods.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations